Pathways in African Philosophical Theology: Augustine Shutte (1938-2016) and Gerrit Brand (1970-2013) - Delport, Dr. Khegan M. (Stellenbosch Theological Journal, 2022)
The article seeks to describe one trend within the theological scene in South Africa, a trajectory that could be called "African Philosophical Theology". In the first part of the article, some methodological problems surrounding such a descriptive category are discussed. Thereafter, I attempt to give a summary of the contributions of two thinkers could be grouped within this category, namely Augustine Shutte (1938-2016) and Gerrit Brand (1970-2013). In this regard, Shutte's approach can be viewed as a philosophical synthesis of Thomistic and African accounts of personhood, while Brand's constitutes a meta-theology, a postfoundationalist attempt to articulate those criteria that are fundamental to adjudicating doctrinal and religious change. While their respective projects are distinctive, I argue that both of them can be classified as practicing a variety of metaphysics and theology that takes seriously the deliverances of African thought, performing thereby a "decolonial" gesture within philosophical theology.